2008
DOI: 10.5194/angeo-26-3623-2008
|View full text |Cite
|
Sign up to set email alerts
|

PFISR nightside observations of naturally enhanced ion acoustic lines, and their relation to boundary auroral features

Abstract: Abstract. We present results from a coordinated camera and radar study of the auroral ionosphere conducted during March of 2006 from Poker Flat, Alaska. The campaign was conducted to coincide with engineering tests of the first quarter installation of the Poker Flat Incoherent Scatter Radar (PFISR). On 31 March 2006, a moderately intense auroral arc, (∼10 kR at 557.7 nm), was located in the local magnetic zenith at Poker Flat. During this event the radar observed 7 distinct periods of abnormally large backscat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 49 publications
4
28
0
Order By: Relevance
“…48 events of spectral enhancements and their corresponding average profiles of plasma parameters remained. As suggested by the observations of Michell et al (2008Michell et al ( , 2009) and Michell and Samara (2010), there is a possible connection between auroral activity and the type of ion line enhancements presented here. The K index is a measure of magnetic disturbance and in order to quantify a possible relation to auroral activity, the K index was noted for each event.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…48 events of spectral enhancements and their corresponding average profiles of plasma parameters remained. As suggested by the observations of Michell et al (2008Michell et al ( , 2009) and Michell and Samara (2010), there is a possible connection between auroral activity and the type of ion line enhancements presented here. The K index is a measure of magnetic disturbance and in order to quantify a possible relation to auroral activity, the K index was noted for each event.…”
Section: Discussionmentioning
confidence: 75%
“…NEIAL are often seen simultaneously over a height range of several 100 km (e.g., Rietveld et al, 1991) and have been observed up to 1900 km altitude (Ogawa et al, 2006). Michell et al (2008) reported observations of enhanced ion lines at low altitudes (250-350 km) made with the Poker Flat Incoherent Scatter Radar (PFISR). Using long uncoded pulses, their range resolution was limited to 75 km, which roughly coincided with the altitude range of the enhancements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The altitude extent of regions with enhanced backscattered radar power is limited to about 2 km in our observations. While unresolved, the altitude extent has been reported to be ∼ 10 km (Isham et al, 2012) and 72 km (Akbari et al, 2012;Michell and Samara, 2010;Michell et al, 2008) in recent observations of a enhanced zero Doppler shift features. More common observations of NEIALs, where no zero Doppler shift feature is observed, typically extend over hundreds of kilometers and have been related to dynamic aurora exhibiting fine-scale structuring.…”
Section: Discussionmentioning
confidence: 99%
“…Among the models for NEIALs, the Langmuir turbulence model and the model proposed by Ekeberg et al (2010) the enhanced ion line shoulders (Michell et al, 2008;Michell and Samara, 2010;Ekeberg et al, 2010;Akbari et al, 2012), the enhanced radar spectra reported herein and those reported by Isham et al (2012) show a distinct zero Doppler shift feature. A distinct zero Doppler shift feature is only accounted for in LT models.…”
Section: Discussionmentioning
confidence: 99%